Cigarette Taxes and Smoking among Sexual Minority Adults - Christopher S. Carpenter; Dario Sansone (Institute of Labor Economics (IZA), 2020)
We provide the first quasi-experimental evidence on the relationship between cigarette taxes and sexual minority adult smoking by studying individuals in same-sex households (a large share of whom are in same-sex romantic relationships) from the 1996-2018 Behavioral Risk Factor Surveillance System. We find that cigarette taxes significantly reduced smoking among men and women in same-sex households, and the effects we find for men in same-sex households are significantly larger than the associated effects for men in different-sex households (the vast majority of whom are heterosexual married/partnered men). This result suggests that the sizable disparities in adult smoking rates between heterosexual and sexual minority men would have been even larger in the absence of stricter tobacco control policy. In line with previous research indicating that cigarette taxes have 'lost their bite', we find no significant relationship between cigarette taxes and sexual minority smoking in more recent years.
Keywords: H20; H71; I12; I18; 330; LGBT; cigarette tax; health disparities